Collaborative Governance in Palm Oil Permit Enforcement: Anti-Corruption Supervision, Indigenous Rights, and Sustainable Development in West Papua - Linda Novi Trianita; Vishnu Juwono (Politeknik Siber Cerdika Internasional, 2026)
Background: Drawing on the integrative framework of collaborative governance developed by Emerson, Nabatchi, and Balogh, the article analyzes how provincial and district governments, the Corruption Eradication Commission (KPK, civil society organizations, technical experts, and Indigenous communities interacted in the review and revocation of problematic plantation licenses. Objective: This article examines how collaborative governance shaped palm oil permit enforcement in West Papua, Indonesia, during the implementation of the province’s palm oil governance moratorium. Methods: The study used a qualitative case study approach based on interviews with 12 key informants selected through purposive sampling, policy documents, legal-administrative materials, and field narratives from government, civil society, expert, anti-corruption, and community actors. Results: The findings show that collaboration emerged because palm oil licensing problems cut across administrative, legal, spatial, environmental, fiscal, and customary land dimensions. The KPK played a crucial role as a supervisory and accountability-inducing actor, while EcoNusa and technical experts strengthened legal, spatial, and social analysis. In Sorong Regency, collaboration resulted in concrete administrative actions, including company clarification, action plans, and permit revocation. However, the durability of collaborative outcomes was constrained by fragmented licensing data, limited institutionalization, litigation risks, and insufficient integration of Indigenous communities as rights-bearing subjects. Conclusion: The article contributes to collaborative governance literature by showing that, in resource frontier contexts, collaboration must be assessed not only through coordination and joint action but also through legal durability, Indigenous rights recognition, and post-revocation socio-ecological restoration. This study extends previous collaborative governance research by introducing legal durability as a novel evaluative dimension applicable to natural resource permit enforcement contexts.